Exploring Targets of Cell Wall Protein Synthesis and Overexpression Mediated Drug Resistance for the Discovery of Potential M. tb Inhibitors - Nandi, Sisir; Saxena, Anil K. (Current Topics in Medicinal Chemistry, 2021)
Tuberculosis is an infectious disease engulfing millions of lives worldwide; it is caused by mammalian Tubercle bacilli, Mycobacterium tuberculosis complex, which may consist of strains viz. M. tuberculosis hominis (human strain), M. microti, M. pinnipedii and M. canettii. The other pathogenic strain is M. africanum, which belongs to the M. tuberculosis complex and it is fully virulent for humans. The non-pathogenic strains in the complex may include M. fortuitum and M.smegmatis. Extensive research has been carried out to combat this dangerous disease. World Health Organization proposed Directly Observed Treatment Short-course regimen (DOTS) for the eradication of TB. In addition, the compounds such as TBA-7371, TBI-166, AZD5847 and PBTZ-169 are under clinical trials whereas the recently FDA-approved anti-tubercular drugs are Pretomanid (PA-824), Bedaquiline (TMC207), Linezolid (PNU-100480) and Delamanid (OPC-67683). The early detection of mycobacterium tuberculosis can be permanently cured by DOTS comprising Pyrazinamide (Z), Isoniazid (H), Rifampin (R) and Ethambutol (E). The duration of treatment depends on the viability of the disease. DOTS can target to disrupt the biosynthesis of mycobacterial cell wall proteins expressed by various genes. Overexpression of these genes may produce drug-resistant due to dose misuse or the intake of quality compromised anti-tubercular drug regimen. Therefore, in the present review, there has been a necessity to report the second line anti-tubercular chemotherapeutics to target various proteins which are the building blocks of M. tb cell wall, overexpression of which may produce drug resistance.
Keywords: Mycolic acid